Influence of Succession Program on the Growth of Church Projects in Evangelical Lutheran Church of Tanzania in Northern Diocese (Indian Journal of Management and Language (IJML), 2025)
The study aimed to examine the influence of succession planning on the growth of the Evangelical Lutheran Church of Tanzania in Northern Diocese church projects. A cross-sectional research design was used, with 264 samples from registered employees and project management selected through random and purposeful sampling. Data collection was conducted through questionnaires and in-depth interviews, with face-to-face interviews with 12 management. The study was conducted ethically, ensuring participant privacy and confidentiality. The study considered reliability and validity where a pre-test for internal consistency obtained 0.78 Cronbach’s alpha coefficient that indicated the items were measuring the same context. Data was analyzed using SPSS through descriptive statistics and measure of central tendency. The results revealed that the succession planning program is not well-structured, regularly reviewed, and updated. The majority of the respondents showed no active involvement of the church's leadership in supporting and promoting the program, and no preparation of potential leaders for adequate resources and training to ensure the continuity and sustainability of church projects. The current project does not lead to projected growth, as leadership does not support or promote the succession planning program. The study recommends that the church leadership and stakeholders critically evaluate and reassess the existing succession planning program, actively involving the church leadership in supporting and promoting the program, and effectively identifying and preparing potential leaders.